PENGAMBILAN SUMPAH UNTUK BUKTI BARU DARI TERMOHON PENINJAUAN KEMBALI PERKARA PERDATA - Sobari, Ahmad (Universitas Nasional, 2022)
AbstractSubmitting a judicial review (PK) at the Supreme Court, both criminal and civil cases, one of the material requirements is the discovery of new evidence or fresh fact or new circumstances, called novum. The material reason for the Judicial Review (Peninjauan Kembali) of criminal cases is called